Manajemen Sekolah Berbasis Data Sosial-Budaya Membangun Identitas, Kohesi, dan Regulasi Emosi Siswa - Evi Fitriyanti; Tanti Ardianti; Sumaryati Tjitrosumarto; Dwi Prasetyo Rini; Valentino Isnaldianto (Universitas Indraprasta PGRI, 2026)
School management in Indonesia still tends to focus on administrative and academic aspects, while the utilization of students' socio-cultural data has not been systematically integrated into school management. This study aims to explore school management practices based on socio-cultural data in building students' cultural identity, strengthening social cohesion, and developing students' emotional regulation. The study used a qualitative approach through interviews. Data analysis was conducted thematically following Creswell's stages with the assistance of NVivo 12 software. The results show that socio-cultural data is used as a basis for planning contextual and responsive school policies, learning, and services. This practice contributes to the formation of inclusive students' cultural identity, strengthening social cohesion, and developing emotional regulation through a supportive school climate. The implementation of this approach is supported by the commitment of leaders and collaboration of educators, but still faces limitations in competency and an integrated data collection system.